Bullying na adolescência e sua relação com problemas decomportamento, sintomas depressivos e habilidades sociais - Isabela Maria Pinto Goes (2013)
Bullying has been considered as one of the most worrisome issues among children and adolescents, which justifies the use of precise, valid instruments to measure it. This study sought to adopt and validate a multidimensional, bullying self-report tool, as well as to investigate the association of bullying with depressive symptoms, behavioral issues, and a range of social abilities in a sample of Brazilian adolescents. The Adolescent Peer Relations Instrument (APRI) has been translated into Portuguese and culturally adapted to Brazil. On the next stage of the study, students responded to this scale along with the Child DepressionInventory ( = 0,794), the Strengths and Difficulties Questionnaire ( = 0,704) and the Inventory of Social Abilities for Adolescents (frequency = 0,933; difficulty = 0,940). There were 246 students between the ages of 12 and 18 (Average 15,75 years and standard deviation = 1,821), being 58,5% female individuals. A factor analysis was performed throughthe Maximum Likehood method and the results have indicated a bifactor solution, represented by 18 items, each. The bifactor structure has explained 45,4 % of the total variance, with an internal consistency index = 0,928 (Alfa Cronbach), showing that the APRI has acceptable psychometric parameters , being them adequate to identify both bullyingand victimization behaviors. The main results have shown that: a) boys were more engaged as actors in bullying-related behaviors when compared to girls; b) younger adolescents perform physical bullying more frequently than older adolescents; c) adolescents involved in bullying episodes have shown more depressive symptoms; d) there is a positive correlation between bullying and behavioral issues; e) there is a negative association between bullying and prosocial behavior; f) subclasses of social abilities (affective approach and civility) haveshown to be correlated positively to bullying.